Improvement of myocardial fibrosis injury by Shengmai injection in ischemia-induced heart failure in a rat model - Yurong Ding; Junying Wei; Enhui Ji; Menglan Wang; Yue Wu; Mengli Chang; Yi Zhang; Jing Xu (Science of Traditional Chinese Medicine)
Abstract. Background. Heart failure (HF) is the leading cause of death worldwide. Myocardial infarction (MI) is a major contributor to HF. Shengmai injection (SMI) has exhibited protective efficacy in preventing HF. However, the advantages of SMI in the progression of MI-induced HF remain unclear. Objective. To reveal the advantages of SMI in the progression of MI-induced HF. Methods. The differently expressed proteins in rat models with ischemia at the 7th, 14th, 21st, and 28th days were obtained from PubMed. The “compound-target” network of SMI was constructed via the Bioinformatics Analysis Tool for Molecular mechANism of Traditional Chinese Medicine database. The protein-protein interaction relationship was constructed, and biological function was applied to evaluate the advantage effect of SMI in the progression of MI-induced HF. In addition, the prediction results were validated in rats with left anterior descending coronary artery ligation. The cardiac function and heart performance were observed via echocardiography, hematoxylin-eosin staining, and Masson staining, and the levels of procollagen type I carboxy-terminal propeptide, recombinant versican (VCAN), and collagen 1A1 (COL1A1) were measured via enzyme-linked immunosorbent assay in rat plasma. In vitro, H9c2 cells were treated with Angiotensin II (Ang II), and the cell viability, the level of reactive oxygen species (ROS) and Ca2+, and the expression of ANP and connective tissue growth factor were evaluated. Furthermore, the schizandrin A was identified as one of the possible key compounds. After schizandrin A treatment, the level of ROS and Ca2+ and the expression of COL1A1 and VCAN were evaluated. Results. There were 189 compounds and 1612 targets involved in the “compound-target” network, and an interaction relationship was constructed. According to the top subnetwork, the Gene Ontology annotation revealed that SMI may have an antifibrotic and cardiac protective effect against MI-induced HF. In rats, SMI increased ejection fraction, left ventricular fractional shortening, and cardiac output and decreased fibrosis injury; moreover, SMI decreased the levels of procollagen type I carboxy-terminal propeptide, VCAN, and COL1A1 within 35 days. When compared with the Ang II treatment group, SMI increased cell viability and decreased cellular calcium concentration, ROS generation, and the expression of ANP and connective tissue growth factor in vitro. Furthermore, schizandrin A was discovered to be a possible compound in myocardial protection. Schizandrin A increased cell viability after Ang II treatment while decreasing COL1A1 and VCAN levels. Conclusions. This method demonstrates that SMI has an antifibrotic effect. This study provides a promising perspective on translating omics data to clinical applications, as well as an appealing approach to investigating the precise intervention of a multicomponent drug.